The Energy Graph for Minimum Majority Domination - Jayasimman, Paulraj; G, Jenitha; A, Kumaravel (International Journal of Engineering and Technology, 2018)
In this article we have introduced Minimum majority domination energy graph. A set Â is called a majority dominating set if at least half of the vertices either in or adjacent to the vertices . That is , . The minimum cardinality of a majority dominating set is called majority domination number . We defined majority dominating matrix and its energy values for some classes of graphs. Also some boundaries of Energy value of graph G are obtained.Â